Oil-Water-Rock Interactions and Their Implications for Waterand 1-Pentanol-Assisted Enhanced Oil Recovery in Carbonate Reservoirs - Al Maskari, Nasser Saleh 'Amur (Curtin University, 2021)
Low-salinity waterflooding appears to be a cost-effective and environmentally friendly means to enhanced oil recovery in carbonate reservoirs. Wettability alteration has been identified as an important process during low salinity waterflooding. This research aims to understand the wettability alteration at nano- and sub-pore scale. In addition, this research explores the potential of 1-pentanol to shift wettability with implications for EOR in high temperature and high salinity carbonate reservoirs where low salinity water is not available.